2013
DOI: 10.1111/tmi.12101
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of antenatal common mental disorders, preterm birth and low birthweight: a prospective cohort study in a semi‐rural district of Vietnam

Abstract: Abstractobjectives To examine the association of low birthweight (LBW) and prematurity with clinically significant symptoms of antenatal common mental disorders (ACMDs) during the third trimester of pregnancy in a semi-rural area in Vietnam.methods Prospective community-based cohort study. Severity of ACMD symptoms was assessed with the Edinburgh Depression Scale, low birthweight was defined as below 2500 g, and gestational age was estimated according to last menstrual period. Reproductive and socio-demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
3
33
1
1
Order By: Relevance
“…Women with psychiatric disorders have been shown to be less likely to access prenatal care and are more likely to smoke or use alcohol or illicit drugs during pregnancy [4-6]. The latter was also observed in our data, although we may be subject to underreporting of substance abuse compared to other studies and interview data [17,36]. However, we assume that the most severe cases of substance abuse are reported in the pregnancy-related medical records and most women are truly non-users.…”
Section: Discussionsupporting
confidence: 68%
“…Women with psychiatric disorders have been shown to be less likely to access prenatal care and are more likely to smoke or use alcohol or illicit drugs during pregnancy [4-6]. The latter was also observed in our data, although we may be subject to underreporting of substance abuse compared to other studies and interview data [17,36]. However, we assume that the most severe cases of substance abuse are reported in the pregnancy-related medical records and most women are truly non-users.…”
Section: Discussionsupporting
confidence: 68%
“…The women who were interviewed individually were recruited from a list of participants from a previous study (Niemi et al 2013), where the prevalence of antenatal depression had been assessed. A preliminary analysis in that study found 19 mothers with probable antenatal depression, and of those, the women were selected who lived within a 5 km radius of the community health centre where the interviews were conducted.…”
Section: Participantsmentioning
confidence: 99%
“…The prevalence of anaemia in pregnant women is reported to be up to 53% in some very poor areas [33]. Studies have consistently provided evidence for high prevalence of CMD in women during pregnancy and after childbirth, in particular in the least well-resourced rural areas [34-36]. …”
Section: Introductionmentioning
confidence: 99%